The Use of Sentinel Lymph Node Biopsy in BRCA1/2 Mutation Carriers Undergoing Prophylactic Mastectomy: A Retrospective Consecutive Case-Series Study. (1st January 2018) - Câmara, Sara; Pereira, Daniela; André, Saudade; Mira, Beatriz; Vaz, Fátima; Oom, Rodrigo; Marques, José Carlos; Leal de Faria, João; Rodrigues dos Santos, Catarina
Abstract : Introduction . Sentinel lymph node biopsy in prophylactic mastectomy is controversial. It avoids lymphadenectomy in occult carcinoma but is associated with increased morbidity. Women with BRCA mutations have a higher incidence of occult carcinoma and our objective was to assess the clinical utility of sentinel lymph node biopsy when these women undergo prophylactic mastectomy. Materials and Methods. Seven-year retrospective consecutive case-series study of women, with a BRCA deleterious mutation, admitted to prophylactic mastectomy, at our center. Breast MRI < 6 months before surgery was routine, unless contraindicated. Results. Fifty-seven patients (43% BRCA1; 57% BRCA2) underwent 80 prophylactic mastectomies. 72% of patients had had breast cancer treated before prophylactic mastectomy or synchronously to it. The occult carcinoma incidence was 5%, and half of the cases were invasive. SLNB was performed in 19% of the prophylactic mastectomies; none of these had tumor invasion. Women with invasive carcinoma who had not undergone sentinel lymph node biopsy were followed closely with axillary ultrasound. The median follow-up was 37 months, with no local recurrence; 1 patient died of primary tumor systemic relapse. Conclusions. Our data do not support this procedure for routine (in agreement with previous literature), in this high risk for occult carcinoma population.